The Implementation of Providing Performance Allowance Policy in the Secretariat of the General Election Commission Kota Ternate, Indonesia - Eko Ady Prabowo; Muhlis Hafel; Agus Joko Purwanto; Anfas Anfas (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to evaluate the implementation of the policy of providing performance allowance to employees at the Secretariat of the General Elections Commission (GEC) Kota Ternate, as well as their supporting and obstacle factors. This research is a descriptive qualitative research by using case study. The research data were obtained from informants who were respondents, ranging from staff to officials at the Secretariat of the General Elections Commission Kota Ternate. The results of the study showed that although the implementation of the performance allowance was already running there were still some deviations in its management, namely: 1) no socialization or training was held on the management of performance allowance involving GEC Kota Ternate; 2) there is no appointment of a performance allowance management officer, namely the Performance Allowance Management Officer or the control book Management Officer, therefore, it happens overlap working with routine treasurer; 3) there is not a standard operating procedure (SOP) as an assessment standard that aims to provide an assessment and sanctions against employees who do not carry out their duties and functions.